2017
DOI: 10.1158/1055-9965.epi-17-0360
|View full text |Cite
|
Sign up to set email alerts
|

Novel Gene and Network Associations Found for Acute Lymphoblastic Leukemia Using Case–Control and Family-Based Studies in Multiethnic Populations

Abstract: Background Acute lymphoblastic leukemia (ALL) is the most common childhood cancer, suggesting that germline variants influence ALL risk. Although multiple genome-wide association (GWA) studies have identified variants predisposing children to ALL, it remains unclear whether genetic heterogeneity affects ALL susceptibility and how interactions within and among genes containing ALL-associated variants influence ALL risk. Methods Here we jointly analyze two published datasets of case-control GWA summary statist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…We tested for shared and divergent enrichment of association with a trait of interest at the gene-level among interacting genes using network propagation of gene- ε gene-level association statistics as input to Hierarchical HotNet 61 . Hierarchical HotNet identifies significantly altered subnetworks using gene-level scores as input; in this study, these gene scores were set to − log 10 -transformed p -values of gene- ε gene-level association test statistics (see also Nakka et al 56, 105 ). For each ancestry-trait combination, we assigned p -values of 1 to genes with p -values greater than 0.1 to make the resulting networks both sparse and more interpretable (again see Nakka et al 56, 105 ).…”
Section: Online Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested for shared and divergent enrichment of association with a trait of interest at the gene-level among interacting genes using network propagation of gene- ε gene-level association statistics as input to Hierarchical HotNet 61 . Hierarchical HotNet identifies significantly altered subnetworks using gene-level scores as input; in this study, these gene scores were set to − log 10 -transformed p -values of gene- ε gene-level association test statistics (see also Nakka et al 56, 105 ). For each ancestry-trait combination, we assigned p -values of 1 to genes with p -values greater than 0.1 to make the resulting networks both sparse and more interpretable (again see Nakka et al 56, 105 ).…”
Section: Online Materials and Methodsmentioning
confidence: 99%
“…Hierarchical HotNet identifies significantly altered subnetworks using gene-level scores as input; in this study, these gene scores were set to − log 10 -transformed p -values of gene- ε gene-level association test statistics (see also Nakka et al 41, 43 ). For each ancestry-trait combination, we assigned p -values of 1 to genes with p -values greater than 0.1 to make the resulting networks both sparse and more interpretable (again see Nakka et al 41, 43 ). In addition, ancestry-trait pairs in which less than 25 genes produced gene- ε p -values less than 0.1 were discarded as there were an insufficient number of gene-level statistics to populate the protein-protein interaction networks.…”
Section: Methodsmentioning
confidence: 99%
“…PEGASUS, developed by our group (Nakka et al 2016(Nakka et al , 2017, models correlation among genotypes in a region using linkage disequilibrium, the same model as VEGAS (Liu et al 2010) and SKAT without weighting rare variants (Wu et al 2011). PEGA-SUS, by contrast, achieves up to machine precision in gene-level association statistic computations via numerical integration.…”
Section: Overview Of Wings Pipelinementioning
confidence: 99%
“…To identify genetic architectures shared across a set of phenotypes, we aggregate SNP-level association statistics using PEGASUS (Nakka et al 2016(Nakka et al , 2017. PEGASUS can calculate a region-level association p-value for any set of the user-defined genomic region or compute gene-level association statistics.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, more recent computational approaches have expanded the additive GWA framework to aggregate across multiple SNP-level association signals and test for the enrichment of genes and pathways [50][51][52][53][54][55][56][57][58][59][60][61]. In Nakka et al [62] we showed that enrichment analyses applied to multiple ancestries can identify genes and gene networks contributing to disease risk that ancestry-specific enrichment analyses fail to find. Recent multiethnic GWA studies have also found that using non-European populations offer new insights into additive genetic architecture [63][64][65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%